Electronic Service Quality and Participant’s Trust in Encouraging PT. Astra Life Insurance Purchase Decisions in DKI Jakarta - Irma Situmorang (Budapest International Research and Critics University, 2022)
Business competition in the era of globalization is very competitive, both in domestic and international markets. Basically, every human being in his life will face risks. Quality of Electronic Services is a “potential strategic weapon to beat competitors. The increasingly critical customer situation in terms of quality forces the company to